THE SIGNIFICANCE OF PHYSICAL CULTURE AS A COMPONENT OF PREPARING SCHOOLCHILDREN FOR FUTURE MILITARY SERVICE (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines key aspects of the necessity and importance of developing physical qualities in pupils of general secondary education institutions in Ukraine (hereinafter referred to as GSEIs) as a component of their potential readiness for future military service and the defence of their state’s independence and territorial integrity. The text places particular emphasis on the pivotal role of motivation in encouraging students to participate in various physical activities during physical education classes and in after-school settings. It is posited that the efficacy of this work is contingent upon the establishment of an environment within general secondary education institutions that is conducive to the pursuit of physical activity by schoolchildren. This environment must be characterised by interest, utility, and accessibility. The realisation of this environment can be facilitated by the collaborative endeavours of district education, youth, and sports departments; the leadership of territorial communities; and the administrations of general education institutions. Additionally, the dedicated and persistent educational activities of physical education teachers in schools, gymnasiums, and lyceums are instrumental in fostering a culture of physical activity among schoolchildren.The body of the article goes on to discuss the problem of military-patriotic and physical education in schools, a tradition deeply rooted in the historical and pedagogical context of the Ukrainian education system. A thorough analysis of literary sources reveals that over the past several decades, there has been a gradual evolution in the understanding of physical culture as a fundamental component in preparing schoolchildren for future military service, both within the realm of scientific research and state policy. A thorough examination of literary sources reveals that physical culture exerts a significant influence in preparing schoolchildren for military service. The programme has been proven to facilitate the development of fundamental physical qualities, psychological endurance, social cohesion, and leadership traits. However, in order to enhance the efficacy of the process, it is imperative to undertake comprehensive empirical studies that integrate pedagogical, psychological, and physiological measurements. This scientific problem is of relevance and requires further research. In the near future, it may be beneficial to develop an integrated model for motivating senior secondary school students. This model would systematically combine physical culture as a means of developing determination, strength, endurance, discipline, and self-confidence, and military-patriotic education as a source of meaning, values, and a deep understanding of the high value of military service. A promising direction is the improvement of theoretical models for integrating physical, moral-volitional, and civic-patriotic training into a unified system of educational influence, ensuring the development of comprehensive readiness to defend the Motherland. It is also necessary to clarify the conceptual and categorical apparatus of the study, in particular, to define the essence of such phenomena as ‘readiness for military service’, ‘military-applied competence’, and ‘patriotic orientation of physical education’.
Keywords: readiness training; military service; military-patriotic education; general secondary education institution; physical culture; Ukraine